Leadsx2030 Annual Report Year 1 - Byrne, Julie (My University, 2025)
The ADS Annual Report Year 1 (D2.3) delivers a comprehensive analysis and strategic recommendations for stakeholders engaged in advancing Advanced Digital Skills (ADS) across Europe. Building on the ADS analytical framework (D2.1), this report draws on data collected through a mixed-methods approach: a complete survey of all 32 DIGITAL-SO4 funded actions (20 Specialised education programmes and 12 Short-Term Training courses funded between 2021 and 2022) and in-depth interviews with 18 project coordinators (representing 55–58% of both types of projects). The report begins by establishing the context and objectives, underscoring its role in evaluating, informing, and strengthening ADS initiatives. It details the rigorous research methodology that combines quantitative survey results with qualitative insights from interviews. The findings provide a clear picture of the current DIGITAL-SO4 project portfolio, highlighting significant progress and innovative approaches in ADS education design and delivery. They also identify persistent challenges and offer evidence-based solutions.
PUBLISHED
Education and training policy regarding supply of advanced digital skills.